การปรับสภาพของวัตถุดิบดินเซรามิกให้เหมาะสมสำหรับการพิมพ์ด้วยเครื่องพิมพ์ 3 มิติ - ณัฐฌา ชมะสุนทร (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
This research presents a study on the development of ceramic pastes materials for optimum properties for 3D printing using the materials extrusion technique. The rheology properties of ceramic pastes are of great importance for printing materials; ability to maintain shape, volumetric shrinkage, and aesthetics of ceramic surfaces. This requires the addition of chemicals as additives to enhance the material s good appearance. This study has tried mixing pastes in many formulas with different proportions of clay and water. As a result, the clay to water ratio of 72 : 28 is the optimal ratio for 3D printing, but there are still other issues that adjusting amount of water is not enough. Two types of additives commonly used in the ceramic industry, Sodium Polyacrylate and Polyethylene Glycol, were studied. The results were as follows: sodium polyacrylate at a concentration of 0.2% and polyethylene glycol at 1.0-2.0% were optimal conditions. Sodium polyacrylate acts as a dispersing agent for clay particles, resulting in that the pastes having higher clay particle density with less water content, large pores were reduced, and shrinkage occurred less. However, if the concentration exceeds 0.2%, the paste was so hard that it cannot be printed out. Polyethylene glycol enhances the plasticity properties of pastes and gave many positive effects including softening the pastes, easy to print, and smooth the surface of the ceramic. Moreover, if the concentration is too high and the stability of the paste was less, resulting in distorted shape and more contraction. Therefore, in the development of the ceramic pastes in this study, both additives were used together with the reduction of water content for achieving balanced results. Formula 2 can provide the properties mentioned above. The optimal ratio of clay to water was 75 : 25, sodium polyacrylate 0.2%, and polyethylene glycol 1.0%. Moreover, the clay still had minor defects in that the pastes became harder after adjusting these factors, so an increase in the concentration of polyethylene glycol by 1.5% is expected to make the formulation ready to use.